Can we replace computed tomography angiography by contrast-enhanced ultrasound in the surveillance of patients submitted to aortoiliac aneurysm repair?. (August 2022) - Park, Jong Hun; Filho, Alvaro Razuk; Pires, Ana Paula M; Telles, Gustavo José P; Esteves, Fernando P; Caffaro, Roberto Augusto; Parrillo, Eduardo F
Objectives: This study was designed for evaluation of CEUS (contrast-enhanced ultrasound) for the detection of endoleaks after EVAR (endovascular aortic aneurysms repair) as an alternative to CTA (computed tomography angiography), the gold standard in post-EVAR surveillance. Methods: Post-EVAR surveillance of patients who underwent CEUS and CTA was retrospectively analyzed to compare the accuracy of CEUS compared to CTA. For that, the following parameters were analyzed: the largest aneurysm diameter, type of endoleaks, and the time elapsed after EVAR using both surveillance tests. Results: The study involved 110 pairs of exams in patients with infrarenal aortoiliac or isolated iliac artery aneurysm, covering predominantly a male population (89%). The time elapsed after EVAR using CEUS or CTA exams were statistically similar, ranging from one to 58 months (mean 12.2) and one to 65 months (mean 9.7), respectively ( p = 0.124). CEUS sensitivity was 75.5%, specificity 96.7%, false positives were 24.5%, and false negatives were 3.3%. The accuracy between the two exams was 87.3%. A secondary analysis, comparing CTA with CEUS as a reference standard, revealed CEUS sensitivity of 24.5%, higher than CTA for detecting endoleaks, with a concordance rate of true positive results of 75.5%. Among the endoleaks detected solely by CEUS (12 cases), one case was type Ia and eleven were type II, while those detected only by CTA (2 cases), one was type Ia and one type II. Additionally, a type II endoleak associated with type Ib, identified by CEUS, was seen as type II for CTA only. There was no difference between the pre-EVAR and the post-EVAR diameters of aortoiliac aneurysm ( p = 0.058), both for CEUS and CTA. Computed tomography angiography, on the other hand, showed significant aneurysm diameter reduction compared to CEUS for isolated iliac artery aneurysms ( p < 0.001). Conclusion: Contrast-enhanced ultrasound was more effective than CTA in identifying and characterizing endoleaks in patients undergoing EVAR, especially type II endoleaks. The advantages include efficacy and, particularly, safety, and must be considered in EVAR surveillance protocols so that its use becomes widespread. We understand that CEUS, as a surveillance exam, considerably reduces risks to patients compared to CTA.